2019
DOI: 10.1159/000502374
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Bleomycin Toxicity with PET-CT?

Abstract: Aim: Bleomycin is an antitumor antibiotic used successfully to treat a variety of malignancies, predominantly germ cell tumors and Hodgkin’s lymphoma (HL). The major limitation of bleomycin therapy is the potential for life-threatening interstitial pulmonary fibrosis. Early identification of asymptomatic patients who may develop toxicity is important. We aimed to evaluate fluorodeoxyglucose positron-emission tomography (FDG-PET/CT) findings to predict bleomycin toxicity (BT) early after chemotherapy with doxor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Data on the benefits of PET scan in the early detection of BLT are rare and contradictory. Since BLT leads to diffuse hypermetabolism of the pulmonary parenchyma [ 40 , 41 ], some authors have suggested that intermediate PET scans after two or four cycles might be an effective means of early detection of BLT before the onset of clinical symptomatology and radiological signs [ 9 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the benefits of PET scan in the early detection of BLT are rare and contradictory. Since BLT leads to diffuse hypermetabolism of the pulmonary parenchyma [ 40 , 41 ], some authors have suggested that intermediate PET scans after two or four cycles might be an effective means of early detection of BLT before the onset of clinical symptomatology and radiological signs [ 9 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a reliable diagnostic tool, BLT is a diagnosis of exclusion that is based on an array of clinical and radiologic arguments and respiratory function testing data (including decline in diffusing capacity of the lungs for carbon monoxide [DLCO]) and exclusion of other infectious, cardiac, post-radiation and drug (other than bleomycin) etiologies [ 7 - 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The uptake of 2-deoxy-2-[ 18 F]fluoro-d-glucose ( 18 F-FDG) reflects glucose metabolism, not only in inflammatory and malignant tissues but also in healthy tissues (HTs) such as lung, myocardium, liver, spleen and bone marrow. Several studies have reported 18 F-FDG uptake using PET/computed tomography (PET/CT) in HT either before or during treatment to be linked to different factors including potential treatment-related adverse events [1][2][3][4][5]. Monitoring cancer response to therapy as well as their effects on HTs has become even more relevant with the increasing use of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Series of case reports involving patients undergoing chemotherapy offer insight regarding the potential usefulness of HRCT with FDG-PET in the management of DIILD. During follow-up for assessment of treatment outcomes, new areas of FDG uptake in the lung parenchyma should alert the clinician as they likely represent early stages of an inflammatory process prior to the appearance of symptoms or notably HRCT abnormalities (Paschali et al, 2017 ; Beyhan Sagmen et al, 2019 ). On the other hand, pulmonary lesions showing signal attenuation could represent resolution of the disease or progression to fibrosis (Taywade et al, 2016 ; Paschali et al, 2017 ).…”
mentioning
confidence: 99%